Analisis Sentimen Masyarakat terhadap Keamanan Penggunaan E-Commerce B2C Menggunakan Pendekatan Naïve Bayes Berbasis Text Mining untuk Mencegah Penipuan - Marcelena Vicky Galena; Adnan Syawal Adilaha Sadikin; Aprilia Prastyaningrum; Reza Febrian Nugroho; M. Fariz Fadillah Mardianto (G-Tech: Jurnal Teknologi Terapan, 2024)
The Society 5.0 Era's technology development has shifted marketing communication from face-to-face to screen interaction, like online shopping via e-commerce. According to Statista Market Insight data, e-commerce users in Indonesia reached 178.94 million in 2022, with transactions totaling Rp476.3 trillion. Despite its growth, e-commerce is prone to cybercrime, with 16,845 reports to the National Police's Ditipideksus from 2017 to 2020. This research analyzes public sentiment on e-commerce security through Play Store and App Store comments. The Naïve Bayes model shows an accuracy of 80% on the Play Store and 87% on the App Store, with AUCs of 0.864 and 0.942, respectively, indicating excellent sentiment classification performance. The findings aim to help B2C e-commerce providers enhance security through advanced technologies, user education, fraud detection systems, and improved transparency and response to security incidents, thereby increasing user trust.